A spatial regression analysis of German community characteristics associated with voluntary non-remunerated blood donor rates - Weidmann, Christian; Schneider, Sven; Litaker, David; Weck, Eberhard; Klüter, Harald (Vox sanguinis, 2012)
Background and Objectives Previous studies have shown substantial geographical variation in blood donation within developed countries. To understand this issue better, we identified community characteristics associated with blood donor rates in German municipalities in an ecological analysis. Materials and Methods We calculated an aggregated rate of voluntary blood donors from each of 1533 municipalities in south-west Germany in 2007 from a database of the German Red Cross Blood Service. A multiple linear regression model estimated the association between the municipality-specific donor rate and several community characteristics. Finally, a spatial lag regression model was used to control for spatial autocorrelation that occurs when neighbouring units are related to each other. Results The spatial lag regression model showed that a relatively larger population, a higher percentage of inhabitants older than 30 years, a higher percentage of non-German citizens and a higher percentage of unemployed persons were associated with lower municipality-specific donor rates. Conversely, a higher donor rate was correlated with higher voter turnout, a higher percentage of inhabitants between 18 and 24 years and more frequent mobile donation sites. Conclusions Blood donation appears to be a highly clustered regional phenomenon, suggesting the need for regionally targeted recruiting efforts and careful consideration of the value of mobile donation sites. Our model further suggests that municipalities with a decreasing percentage of 18- to 24-year-olds and an increasing percentage of older inhabitants may experience substantial declines in future blood donations.
Published online 29 April 2011
Gesehen am 30.04.2019